What future for minor fibres? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
What future for minor fibres?Minor natural fibres such as sisal, kenaf and coir were important exports from ACP countries until low-cost syntheticpolypropylene destroyed their markets almost over-night. Ij the last two decades these natural fibres...